THE ROLE OF NEXT-GENERATION SEQUENCING IN LUNG CANCER DIAGNOSIS - Moskalenko, Yuliia; Vynnychenko, Oleksandr; Sulaieva, Oksana; Moskalenko, Roman (Eastern Ukrainian Medical Journal, 2023)
Among all malignant neoplasms, lung cancer is the cause of death in approximately every fifth patient. Next-generation sequencing can solve the issue of not only diagnosis but also the further treatment of lung cancer.Aim. The work aims to search, process, generalize and bibliometrically analyze the scientific literature to study the main trends in next-generation sequencing in diagnosing non-small cell lung cancer.Materials and methods. One thousand nine hundred thirty-one literature sources, including information about next-generation sequencing, were published between 2010 and 2023. The data search was carried out in electronic databases Scopus, PubMed, Web of Science, and Google Scholar using keywords: "lung cancer," "next-generation sequencing," "targeted therapy," "genetic mutations," "circulating tumor DNA," and "liquid biopsy." The authors used the bibliometric tools of the Scopus and SciVal databases to analyze the year, source, type of study, subject area, and country of publication.Results and discussion. Next-generation sequencing is gradually becoming the new diagnostic standard. This technology allows to detect biological markers with high accuracy and specificity. Many studies have confirmed the effectiveness of next-generation sequencing for diagnosing lung cancer, assessing response to treatment and sensitivity to drug therapy, and predicting the prognosis of the disease. Lung cancer is one of the most common tumors with a high mutational load. Unique diagnostic panels allow for a short period to examine tumor tissue for a wide range of biological markers. The article aims to investigate the main areas of application of next-generation sequencing in patients with lung cancer and current clinical trials in this field. The bibliometric analysis of the scientific literature consisted of the study of publication activity from 2010 to 2023, the geography of publications, and the identification of scientific journals where the articles about the role of next-generation sequencing were publicized.Conclusions. Next-generation sequencing is widely used in medicine. This method can become one of the leading methods for diagnosing lung cancer because it can accurately identify specific biological markers. Tumor tissue embedded in paraffin blocks and various biological fluids can be used for diagnosis. Next-generation sequencing is effective even in cases where the amount of tumor tissue is limited and other methods cannot identify it. The advantages of the method are confirmed in clinical trials and described in many scientific publications of the leading countries of the world. As a result, next-generation sequencing appears to be an effective method for diagnosing lung cancer and selecting the most appropriate regimen of targeted or immunotherapy. Disadvantages of the method include the high cost in developing countries and the need for appropriate software.